Influence of corruption on economic growth in Peru 2001-2010. - Olivera Cáceres, Jesús Amadeo (2013)
Objetive: The objective of the research was to determine the influence of corruption on economic growth in Peru. Established the following hypothesis: If corruption is the misuse or abuse of public power for private and personal benefit that affects growth of gross domestic product (GDP). Then in Peru corruption adversely affects economic growth.  Method: The research is documentary, which corresponds to the relational level. The information was obtained through the application of the measuring instrument observation Form, applied the technique of observation, using quantitative scales for variable Economic Growth, measured by GDP, and the variable ordinal scales for Corruption. Result: The results determined that Peru's sustained economic growth in terms of GDP (0.2 to 8.90%). It was found that the index rating of Peru 2001-2010 Corruption was a variation of 4.1 to 3.5; descending since Peru from 44 to 78 in the world ranking of Transparency International. Conclusion: Implying increasing corruption in Peru